PROTECTIVE WASTE: INNOVATION IN ANTI-CORROSION PAINT BASED ON CUCUMBER PEEL WASTE AND TEA POWDER - Gilang Tri Sandi; Erwan Eko Prasetiyo; Amelia Puspa Tamara; Yuniar Istiyani (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Corrosion is a serious problem that can reduce the service life of materials, increase maintenance costs, and reduce the safety level of various construction systems. On the other hand, Indonesia still faces challenges in managing organic waste such as cucumber peels and tea powder that have not been optimally utilized. This research offers an innovative idea in the form of EcoGuard, an anti-corrosion paint based on active extracts from cucumber peel and tea powder waste as an environmentally friendly coating material. The method used is a literature study through searching various scientific publications related to the characteristics of active compounds in cucumber peel and tea powder waste, coating paint formulation, and corrosion resistance testing on metal materials. The results of the literature review show that the antioxidant content, polyphenols, and other organic compounds inboth wastes have the potential to act as natural corrosion inhibitors. This potential utilization is expected to slow down the corrosion rate by tens of percent compared to conventional coatings based on chemicals or heavy metals. This innovation contributes to improving material maintenance efficiency while presenting an environmentally friendly waste-to-product approach. As such, EcoGuard has the potential to become a sustainable coating technologysupporting the achievement of SDG 9 (Industry, Innovation, and Infrastructure), SDG 12(Responsible Consumption and Production), and SDG 13 (Climate Action).